The crucifixion of consumerism and power and the resurrection of a community glimpsed through Meylahn"s wounded Christ in conversation with Rowling"s Christ discourse in the Harry Potter series - Apostolides, Anastasia (HTS teologiese studies, 2014)
Like some fantasies (including Lord of the rings and the Chronicles of Narnia), the Harry Potter series by J.K. Rowling makes a social comment on a particular dominant discourse within a particular sociocultural context. One of Rowling’s social comments is the dehumanising and fragmenting effect of the power and consumerist discourse in Western society – where great value is placed on what a person owns. An example of this theme in the series is the characters of the Dursleys, as prime examples of ‘Muggles’. Although it is not power that Muggles seek, but rather to fit in by having what the Jones’ have, which fits in well with the capitalist discourse as developed by Lacan – as discussed by Meylahn. Rowling juxtaposes this discourse with the alternative sacred story of the Christ discourse (community and fellowship are more important than material possessions), that she has subtly woven into her narrative. This alternative discourse challenges adolescents’ identity and spirituality by offering the Christ discourse as an alternative discourse to the dominant discourse of consumerism and power they live in. In his article, ‘Holistic redemptive pastoral ministry in the fragmented transit hall of existence’, Meylahn (2010) speaks of a ‘wounded Christ’ healing a ‘wounded community’ and this ties in well with the Christ discourse presented by Rowling. Meylahn gives us a useful hermeneutical tool to interpret the actions of some of Rowling’s characters. Hence, Meylahn’s ‘wounded Christ’, will be brought into conversation with the actions of some of Rowling’s characters. By bringing Rowling into conversation with Meylahn, pastors and youth workers are presented with an ideal tool to help guide adolescents towards a more spiritual life that is not bound to the dehumanising discourse of consumerism and power.